1997
DOI: 10.1111/j.1523-536x.1997.00159.pp.x
|View full text |Cite
|
Sign up to set email alerts
|

College Students' Knowledge and Attitudes About Cesarean Birth

Abstract: Background: Numerous clinicians and researchers have expressed concern about the necessity and potential adverse consequences of many cesarean births in the United States. The purpose of this study was to explore college students' attitudes and beliefs about cesarean section. Methods: One hundred two college students (66% women) completed a 20-item questionnaire that asked i f they viewed cesarean delivery as a potentially negative experience, as a normal or acceptable method of childbirth, and as medically ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
3
1
Order By: Relevance
“…A minority of male and female participants expressed a preference for a cesarean delivery (nearly 9%). This rate is somewhat lower than the rate of 13 percent reported in a comparable survey of college students by Lampman and Phelps (15), but significantly higher than the actual prevalence of woman‐initiated cesarean section in British Columbia (20). A retrospective chart review of all nulliparous deliveries at seven British Columbia hospitals between June 1, 2002, and May 31, 2004, revealed a prevalence of woman‐initiated cesarean section of less than 1 percent (20).…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…A minority of male and female participants expressed a preference for a cesarean delivery (nearly 9%). This rate is somewhat lower than the rate of 13 percent reported in a comparable survey of college students by Lampman and Phelps (15), but significantly higher than the actual prevalence of woman‐initiated cesarean section in British Columbia (20). A retrospective chart review of all nulliparous deliveries at seven British Columbia hospitals between June 1, 2002, and May 31, 2004, revealed a prevalence of woman‐initiated cesarean section of less than 1 percent (20).…”
Section: Discussioncontrasting
confidence: 56%
“…Currently, little is known about the childbirth views and birthing preferences of the next generation of women and men most likely to become parents, that is, college‐aged women and men. Few studies of the beliefs and attitudes of this population about reproductive issues were found in the published literature (14–17). Only one study, conducted in 1996, reported the prevalence of cesarean and vaginal birth preferences among reproductive‐aged men and women who had yet to bear children (15).…”
mentioning
confidence: 99%
See 2 more Smart Citations